Primary Malignant Melanoma of the Breast: Mankweng Breast Oncology Experience - Makhubele, Hundzukani Dost; Bhuiyan, Mirza MZU (Jour Med Resh and Health Sci, 2020)
Malignant melanoma is predominantly a cutaneous and mucous membrane disease. In this case report, we seek to explore and share our local experience of primary malignant melanoma of the breast and give a literature review on the standard of care as well as to stimulate physician awareness. Our interest is on the appreciation of the current lack of set guidelines on how to work-up patients that present with this rare variant of malignant melanoma and to highlight its management. We present here a rare case of a 62 years old female with the primary malignant melanoma of the breast (PMMB).